What are the influential factors for emotional regulation? A latent profile analysis based on PISA 2022 Taiwan data - Edward Hung Cheng Su; Chia Hsin Chen (Humanities & Social Sciences Communications)
Abstract Emotional regulation refers to an individual’s ability to manage and respond to negative emotional experiences and stressors in a way that promotes effective emotional functioning and coping. Adolescence is a critical period for the development of emotional regulation, during which students from different backgrounds, such as gender, grade, and economic, social, and cultural status (ESCS) may exhibit different patterns of emotional regulation development. In PISA 2022, stress resistance and emotional control were used to measure emotional regulation. Thus, the aim of the study was to examine the current state of emotional regulation among 15-year-old students in Taiwan using data from PISA 2022 database. First, the study sought to explore different level in emotional regulation across various latent classes through Latent Profile Analysis (LPA). Second, it aimed to investigate the influence of students’ background variables on these latent classes of the emotional regulation through three-step ML method. The key finding of the study are as follows: (1) There was a significant decline in emotional regulation when transitioning between learning stages. (2) Gender was the most significant factor influencing the latent classes of emotional regulation among the students’ backgrounds. (3) Limited effects of ESCS on emotional regulation were found in adolescents. Based on these findings of the study, two suggestions are provided to future education policymakers, general and counseling teachers, as well as education researchers: (1) Creating a supportive and welcoming environment, such as offering lectures and promotional activities, would be beneficial in fostering trust among students (2) It is crucial to teach students how to respect and respond to others’ emotions, regardless of whether they are male or female.